Compósitos preparados a partir de resíduo industrial de couro com elastômeros termoplásticos obtidos através de blendas de polietileno de baixa densidade e borracha natural - Reis, Elton Aparecido Prado dos [UNESP] (2014)
This work aimed at the development of polymr composites by mixing leather waste (RC), to use as filler, with thermoplastic elastomers obtained by the compatibility of low density polyethylene (LDPE) with natural rubber (NR) obtained latex form the rubber tree (NR) obtained latex from the rubber three (Hevea brasileiensis clone), together with curing agents, vulcanizing order to BN, for which thereby obtain the best properties of the material. The samples were produced on a HAAKE torque rheometer using roller type rotors. After the processes of rheometer, samples were pressed to occur term vulcanization of the elastomeric phase and molding of speciments. The TPEs and composites were characterized by means of mechanical, morphological, structural and thermal analysis. Based on these results, we intend to drive new material for technological applications to be used in manufacturing automobile parts, gears, among others. With this new material also pretends to direct an application to the reside of bovide leather, which is an abundant and undersirable material generated in the manufacturing of leather, which can cause serious environmental damage due to the chromium present in its structure